The changing education distribution and income inequality in Great Britain - Iva Valentinova Tasseva (University of Essex, Institute for Social and Economic Research (ISER), 2019)
Over the past years, the number of university graduates increased at an unprecedented rate in Great Britain. We analyse how this higher education (HE) expansion affected inequality in household net incomes in the 2000s. We show that, all else being equal, education composition changes led to higher living standards mostly through higher wages. As HE expansion benefited households from the middle and top of the distribution more than the bottom, income inequality increased. Despite the increasing share of high-educated workers, we find no evidence of a 'compression' effect on inequality, as the HE wage premium remained broadly unchanged.
Keywords: D31; I24; I26; 330; higher education expansion; income distribution; decomposition